Pengembangan Modifikasi Bola Pompa Angin Dalam Permainan Bola Kasti Pada Kelas V SDN Glagahsari 1 Kabupaten Pasuruan - Putra, Amanta Hafiz; Pratama, Indra Gunawan (CV. ITTC INDONESIA, 2024)
The lack of interest among students in the game of kasti is the background problem addressed in this research. The researcher utilized a modified air pump ball as a substitute for a tennisball. The air pump ball is a type of ball made from synthetic rubber, thus eliminating the potential for pain upon impact with the body. The modification of the air pump ball is intended to increase students' interest in playing kasti in the fifth-grade class at SDN Glagahsari 1 in Pasuruan Regency. This research employs the ADDIE model, a development method consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection involves distributing questionnaires to content experts, media experts, small-scale trials, and large-scale trials. Based on the validation results from content and media experts, with each expert scoring 88% and 94%, respectively, it is indicated that the modified air pump ball is valid and suitable for use without revisions. Before conducting the large-scale trial, the researcher distributed before trial questionnaires to assess students' knowledge of softball, revealing an average percentage of 50%, reinforcing the lack of interest among students in the game. After the large-scale trial, after trials questionnaires were distributed, indicating an average percentage score of 90% among students. This demonstrates that the modified air pump ball is highly effective in enhancing students' interest in kasti game in the fifth-grade class at SDN Glagahsari 1, Pasuruan Regency.